Use of Vetiver Zizinioides Floating Beds to Improve the Quality of Surface Water in a Mediterranean Climate - Correia, José; Almeida, Adelaide; Durão, Anabela; Pardal, Ana; Borralho, Teresa (KnE Materials Science, 2022)
Due to the negative effects of its main inflows, the water quality of Roxo stream, located in southern Portugal, an area characterized by Mediterranean climate, is degraded, causing consequences in irrigated agricultural activity. The eco technology of floating beds was used to improve the quality of this water. Three Vetiver zizinioides floating beds (3.3 m2/unit; density 40.5 plants/m2) were placed on the Roxo stream in May 2020 and the water quality was monitored until December 2020 in two places: at the floating beds location and 100 m higher up in the stream. The load mass was calculated for both sampling points and the removal rate for each parameter was monitored. The average removal rates obtained were: (i) TN = 33%; (ii) TP = 43%; (iii) COD = 44%; and (iv) Cl- = 15%. The DO level increased slightly, and the pH remained neutral. Although the water quality improved, the quality was still not high enough to be able to use the water for irrigation and to achieve good ecological status. Keywords: Roxo stream, surface water quality, real scale, floating beds, Vetiver zizinioides